2015
DOI: 10.1007/s11606-015-3500-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Use of Internet and Telephone Medication Refills among Linguistically Diverse Patients

Abstract: BACKGROUND: Health systems are increasingly implementing remote telephone and Internet refill systems to enhance patient access to medication refills. Remote refill systems may provide an effective approach for improving medication non-adherence, but more research is needed among patients with limited English proficiency with poor access to remote refill systems. OBJECTIVE: To compare the use of remote medication refill systems among limited-English-proficiency (LEP) and English-proficient (EP) patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…LEP patients were oversampled to attain representation by each language group, as reflected in the GHC. 6 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LEP patients were oversampled to attain representation by each language group, as reflected in the GHC. 6 …”
Section: Methodsmentioning
confidence: 99%
“…12–14 Prior research examined the relationship between English proficiency and use of Internet medication refill systems, and found that only 21% of LEP patients with chronic illness used the online service, compared to 53% of English proficient patients. 6 This discrepancy is not surprising, given that the majority of refill services through an online patient portal are exclusively delivered in English—but also because LEP patients are affected by many of the aforementioned sociodemographic factors that exacerbate the digital divide (lower education, lower income, foreign-born status, lower literacy levels and decreased access to technology). 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And despite the political rhetoric, the U.S. continues to be a destination for persons around the world, and these immigrants often experience significant health disparities. Moreno et al 3 compared the use of remote medication refill systems among patients with limited English proficiency. They found that while health plans were increasingly relying on remote medication refills, patients whose first language is not English (e.g.…”
mentioning
confidence: 99%
“…
M oreno et al 1 examine the relationship between English proficiency and use of remote medication refill systems (that is, requesting to refill medications through automated phone or online systems rather than in person). They find that only 46 % of limited English proficient (LEP) patients with chronic illness use these services, compared to 83 % of English proficient patients.
…”
mentioning
confidence: 99%